Line of sight stabilization of two-dimensional gimbal platform - Aggarwal S.; Joshi A.; Kamal S. (My University, 2025)
The LOS stabilization control based on gyroscopic stabilized staging is required to disengage the line of sight from the movement and jitter in the carrier and also ensure smooth tracking of target in electro-optical tracking systems. This paper presents a detailed comparison of linear controllers and an intelligent controller (Lead-Lag, Proportional-Integral-Derivative (PID) and Fuzzy Logic controller) for the above mentioned system. The overall control systems have been simulated using MATLAB/Simulink. © 2017 IEEE.